Boosting biomass valorisation. Synergistic design of continuous flow reactors and water-tolerant polystyrene acid catalysts for a non-stop production of esters. Issue 14 (14th June 2018) - Trombettoni, Valeria; Sciosci, Daniele; Bracciale, Maria Paola; Campana, Filippo; Santarelli, Maria Laura; Marrocchi, Assunta; Vaccaro, Luigi
Abstract : A pump-free, waste-minimized flow protocol exploiting the features of a specifically designed heterogeneous catalyst has been defined for a non-stop production of biomass-derived esters. Abstract : An effective flow protocol exploiting the features of a specifically designed solid catalytic system has been defined for the direct esterification of biomass-derived carboxylic acids with structurally diverse alcohols on grams per hour scale and with minimal cost in terms of waste disposal. The potential of the catalyst to work indefinitely under pump-free continuous flow conditions has been explored.